Optimisasi Waktu Pemanasan Tingkat Kesukaan Kecap Kelapa - Siti Fatima; Masriani Masriani; Abdullah Abdullah; Ince Siti Wardatullatifah (Jurnal Ilmu Pertanian Indonesia, 2024)
This study aims to optimize the heating length in terms of the sensory properties of sweet soy sauce made from coconut water. This experiment used a Complete Randomized Design consisting of 7 treatment levels, with each combination of treatments repeated 3 times so that the total was 21 treatments. It was concluded that the length of heating affects the color, taste, and viscosity of sweet soy sauce. Panelists favored the 160-minute warm-up time in terms of color, taste, and viscosity. The color favorability score was 5.64 (like), taste was 4.87 (somewhat like), viscosity was 5.61 (like), and aroma was 5.27 (somewhat like). Keywords: organoleptic, length of heating, sweet soy sauce